Comércio internacional e meio ambiente marinho: a tutela jurídica dos oceanos e a defesa do multilateralismo comercial - Barbosa, Nicole Miranda (2019)
This dissertation aims to study the interactions between international trade and the marine environment, focusing on the negative externalities of the intensification of free trade on marine ecosystems and the impacts caused by protectionist environmental policies on the multilateral trading system, topics of great relevance regarding the extent of its effects in a globalized world. Initially, it intends to address the evolution of the environmental issue throughout history, mentioning the international conferences on the environment and the classification of the environment as a fundamental right. After contextualizing these different phases of environmental protection, in a second moment, this dissertation seeks to analyze the main impacts of international trade on the marine environment, mentioning the importance of the oceans, the international legal protection of the marine environment, the link between free trade and environmental issues and the main impacts caused by the intensification of international trade, explaining issues such as ballast water, oil spills, predatory fishing, flags of convenience and noise pollution in the oceans. In the third and last moment, this dissertation deals with the impacts of environmental policies on the multilateral trading system, discussing the institutionalization of international trade, the classification of WTO as a locus of environmental governance and the issue of environmental barriers to trade, focusing on the study of the Shrimp-Turtle Case, which was a WTO controversy under the DSB. This dissertation was elaborated through the exploratory-descriptive bibliographical research, using the inductive and deductive methods to reach the main conclusions